Tatalaksana Geographic Tongue Akibat Defisiensi Nutrisi: Laporan Kasus - Fauzia Variansiana; Sartari Entin Yuletnawati (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Geographic tongue or benign migratory glossitis is a benign disorder of the oral mucosa that is relatively common in dental practice. This condition is characterized by erythematous areas caused by the loss of filiform papillae surrounded by irregular white borders. To understand the clinical characteristics of geographic tongue and the contributing factors involved in the development of the lesion in order to establish an appropriate diagnosis and provide adequate patient education. A 25-year-old female patient presented with complaints of patches on the tongue for approximately two months. The patient had been following an OMAD (One Meal A Day) diet for one year and reported an allergy to white rice. The patient also had a history of psoriasis. Nutritional deficiencies such as vitamin B complex, vitamin B12, folic acid, iron, and zinc may affect the integrity of the oral mucosa and disrupt the regeneration of the lingual epithelium. These conditions may lead to atrophy of the filiform papillae, resulting in the characteristic erythematous appearance of geographic tongue. In addition, immunological and inflammatory factors associated with psoriasis are also suspected to contribute to lesion development. Geographic tongue is a benign inflammatory condition with a multifactorial etiology, including nutritional deficiencies and immunological factors such as psoriasis. Evaluation of systemic conditions and nutritional status is important to support accurate diagnosis and proper patient management.